The real worlds of welfare capitalism - Goodin, Robert E. (Cambridge University Press, 1999)
This book traces how individuals have fared over ten years in each of the three principal types of welfare state. The authors argue that the social democratic welfare regime of the Netherlands outperforms the corporatist German regime and the liberal US regime on a range of measures.